2013
DOI: 10.7150/ijms.5500
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of TFF1 and Increased Expression of TFF3 in Gastric Cancer: Correlation with Clinicopathological Parameters and Prognosis

Abstract: Objectives: The trefoil factor family (TFF) is composed of three thermostable, and protease-resistant proteins, named TFF1, TFF2 and TFF3, and plays a role in gastrointestinal mucosal defence and repair. Recently, TFFs have been found to be related to the development of various types of cancer. This study assessed the relationship between the expression of TFF1 and TFF3 and the clinicopathological parameters in gastric carcinoma (GC). Materials and Methods: The expression of TFF1 and TFF3 was analyzed by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 44 publications
(57 reference statements)
3
44
1
2
Order By: Relevance
“…194 The expression of TFF1 has been reported to be decreased in carcinomas of the stomach and esophagus when compared with normal mucosa. 193,195 In contrast, TFF1 expression in breast cancer is markedly increased. Our recent studies [83][84][85] demonstrated that TFF1 was overexpressed in breast carcinomas and colorectal ADCs; under- expressed in lung ADCs, ovarian carcinomas, and endometrial carcinomas; and was usually absent in germ cell carcinomas, RCCs, and thyroid carcinomas.…”
Section: Review Of Selected Antibodiesmentioning
confidence: 88%
“…194 The expression of TFF1 has been reported to be decreased in carcinomas of the stomach and esophagus when compared with normal mucosa. 193,195 In contrast, TFF1 expression in breast cancer is markedly increased. Our recent studies [83][84][85] demonstrated that TFF1 was overexpressed in breast carcinomas and colorectal ADCs; under- expressed in lung ADCs, ovarian carcinomas, and endometrial carcinomas; and was usually absent in germ cell carcinomas, RCCs, and thyroid carcinomas.…”
Section: Review Of Selected Antibodiesmentioning
confidence: 88%
“…Accumulating evidences manifest that TFF3 may be a causal connection between inflammation and occurrence of GI tumors [24,44,[49][50][51] . A large number of reports have also shown that TFF3 is involved in larger tumor size, tumor cell scattering, angiogenesis, lymph node metastasis, invasion, advanced stage and recurrence [24,[52][53][54][55][56][57][58]. On the contrary, anti-sense TFF3 inhibits cell growth and significantly enhances the apoptosis induced by adriamycin in human GC [59].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pathologic expression of TFF-3 has been observed in several cancers, including endometrial and prostate adenocarcinoma, gastric cancer, and several lung cancer histologic subtypes. [26][27][28] Although there has been considerable focus on the cardiovascular consequences of kidney disease, the importance of non-CVD outcomes as a cause of death in CKD is increasingly recognized. People with CKD experience premature morbidity and death from a wide range of causes compared with age-matched members of the general population.…”
Section: Principle Findingsmentioning
confidence: 99%